Gambaran Pengetahuan dan Sikap Tentang Penggunaan Jamban Sehat pada Ibu Rumah Tangga Kelurahan Kebonwaru, Kota Bandung dengan Menggunakan Media Promosi Kesehatan - Lolan, Yosef Pandai; Akbar, Aulia; Sutriyawan, Agung (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2023)
The use of healthy latrines in the household can prevent diarrhoea, schistosomiasis and other diseases that family members are susceptible to. Based on national cases, 10.50% of the population still defecates in the open. Objective: to obtain an overview of knowledge scores and attitudes towards using healthy latrines before and after being given health education using video media and leaflets. This type of research is a quasi-experiment with a two-group pretest-posttest design. The research population was 3627 households. The sample size technique uses a minimum sample size formula, so the sample size is 24 respondents for the video group and 24 respondents for the leaflet group. The sampling technique in this research is using nonprobability sampling with a purposive sampling method. The instrument used to collect data was a questionnaire. The results showed an increase in the average knowledge score of 3.55. In the second measurement, the average knowledge score was 21.17 with a standard deviation of 2.973, so there was an increase in the average knowledge score of 5.34 and the attitude score before being given the video + leaflet intervention was 109.92 with a standard deviation of 10.562, after given the intervention to 112.54 with a standard deviation of 7.277, there was an increase in the average attitude score of 2.62. It was concluded that the respondents had good knowledge and a positive attitude towards using healthy latrines, but the respondents or the community had not yet implemented the use of healthy latrines.